The Use of Wood Biomass in the Regional System of Renewable Energy Sources as a Chance for the Region - Kluczkowski, Andrzej (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The world needs energy. It is an obvious truth you do not need to prove. The modern world needs the electricity. With advancing civilization and the rate of consumption, and the demand for electricity is growing. At the same time, conventional resources are running out. This situation leads to the search for new renewable sources of energy. Therefore a crucial role of forests should be taken into consideration. The study shows that, in the relatively short term, the wood biomass (mainly forest) will play a significant role in the regional energy system